TRADITIONAL AND ALTERNATIVE THERAPY FOR MENTAL ILLNESS IN JAMAICA: PATIENTS’ CONCEPTIONS AND PRACTITIONERS’ ATTITUDES - James, Caryl C A B; Peltzer, Karl (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The aim of this study was to investigate traditional and alternative therapy for mental illness in Jamaica: patients’ conceptions and practitioners’ attitudes. The sample included 60 psychiatric patients selected from Ward 21 at the University of the West Indies, Kingston as well as Princess Margaret outpatient clinic, and 30 Afro-centric psychiatric nurses, psychiatrist and clinical psychologists from Kingston and St. Thomas, Jamaica. Patients were interviewed with the Short Explanatory Model Interview (SEMI) and practitioners completed a self administered questionnaire on attitudes towards traditional and alternative medicine. Results indicate that among psychiatric patients more than a third expressed the belief that the overall cause of their mental illness was as a result of supernatural factors. In general, the majority of patients felt that their perception of their problems did not concur with the western practitioner, which in turn caused distress for these patients. In case for those who also sought traditional medicine, they were more inclined to feel pleased about their interaction and the treatment they received. Results from western trained practitioners found that although they acknowledged that traditional medicine plays a major role in the treatment of mental illness among psychiatric patients the treatment was not advantageous. For the most part when all three traditional approaches were examined alternative medicine seemed more favourable than traditional healing and traditional herbal treatment. There is a need to develop models of collaboration that promote a workable relationship between the two healing systems in treating mental illness.